EMILIN2 down‐modulates the Wnt signalling pathway and suppresses breast cancer cell growth and migration. Issue 4 (March 2014) - Marastoni, Stefano; Andreuzzi, Eva; Paulitti, Alice; Colladel, Roberta; Pellicani, Rosanna; Todaro, Federico; Schiavinato, Alvise; Bonaldo, Paolo; Colombatti, Alfonso; Mongiat, Maurizio
Abstract EMILIN2 is an extracellular matrix (ECM) protein that exerts contradictory effects within the tumour microenvironment: it induces apoptosis in a number of tumour cells, but it also enhances tumour neo‐angiogenesis. In this study, we describe a new mechanism by which EMILIN2 attenuates tumour cell viability. Based on sequence homology with the cysteine‐rich domain (CRD) of the Frizzled receptors, we hypothesized that EMILIN2 could affect Wnt signalling activation and demonstrate direct interaction with the Wnt1 ligand. This physical binding leads to decreased LRP6 phosphorylation and to the down‐modulation of β‐catenin, TAZ and their target genes. As a consequence, EMILIN2 negatively affects the viability, migration and tumourigenic potential of MDA‐MB‐231 breast cancer cells in a number of two‐ and three‐dimensional in vitro assays. EMILIN2 does not modulate Wnt signalling downstream of the Wnt–Frizzled interaction, since it does not affect the activation of the pathway following treatment with the GSK3 inhibitors LiCl and CHIR99021. The interaction with Wnt1 and the subsequent biological effects require the presence of the EMI domain, as there is no effect with a deletion mutant lacking this domain. Moreover, in vivo experiments show that the ectopic expression of EMILIN2, as well as treatment with the recombinant protein, significantly reduce tumour growth and dissemination of cancer cells in nude mice. Accordingly, the tumour samples are characterized by a significant down‐regulation of the Wnt signalling pathway. Altogether, these findings provide further evidence of the complex regulations governed by EMILIN2 in the tumour microenvironment, and they identify a key extracellular regulator of the Wnt signalling pathway. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.